1998
DOI: 10.1152/jappl.1998.85.6.2054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of localized auxiliary heating on hand comfort during cold exposure

Abstract: There is a need for a hand-heating system that will keep the hands warm during cold exposure without hampering finger dexterity. The purpose of this study was to examine the effects of torso heating on the vasodilative responses and comfort levels of cooled extremities during a 3-h exposure to -15 degreesC air. Subjects were insulated, but their upper extremities were left exposed to the cold ambient air. The effect of heating the torso [torso-heating test (THT)] on hand comfort was compared with a control con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 31 publications
4
35
2
Order By: Relevance
“…Brajkovic et al (1998) define the comfortable temperature for fingers to be greater than 23 0 C. In this study, we attempted to investigate how hand temperatures of 10, 20 and 30 0 C would affect tracking performance Oksa et al (1995) found that muscle performance as measured by mean IEMG activity decreased at a temperature of 10 0 C. Cooling slowed the function of the agonist muscle and decreased its IEMG activity but increased the IEMG activity of the antagonist muscle. Some researchers have reported that the endurance time of sustained, submaximal, voluntary 5 contractions of muscles are temperature dependent, being optimal at peripheral temperatures of 18-26 0 C (Clarke, Hellon and Lind, 1959).…”
Section: Introductionmentioning
confidence: 98%
“…Brajkovic et al (1998) define the comfortable temperature for fingers to be greater than 23 0 C. In this study, we attempted to investigate how hand temperatures of 10, 20 and 30 0 C would affect tracking performance Oksa et al (1995) found that muscle performance as measured by mean IEMG activity decreased at a temperature of 10 0 C. Cooling slowed the function of the agonist muscle and decreased its IEMG activity but increased the IEMG activity of the antagonist muscle. Some researchers have reported that the endurance time of sustained, submaximal, voluntary 5 contractions of muscles are temperature dependent, being optimal at peripheral temperatures of 18-26 0 C (Clarke, Hellon and Lind, 1959).…”
Section: Introductionmentioning
confidence: 98%
“…Even the power supply for hand used during the study was, at present, too large and heavy for extended use. Brajovik et al [11] presented data supporting the use of torso heating rather than extremity heating. They also raised the issue of insidious hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [3][4][5] have proved that the heating efficiency and heating power are the two most important parameters that should be considered during the EHV design process. In this article, we studied the effects of air velocity and clothing combination on the heating efficiency in the cold environment by a thermal manikin.…”
Section: Introductionmentioning
confidence: 99%